Thermal Performance Investigation of Thermoelectric Cooling System with Various Hot-Side Cooling Methods - Prasetyo, Bowo Y; Rosulindo, Parisya P; Wang, Fujen (UI Scholars Hub, 2024)
Thermoelectric devices have been widely used in various applications, including cooling and power generation. The potential application of thermoelectric cooling systems has been studied. However, these systems still face challenges in achieving optimal performance compared with other cooling systems. Several factors, including the hot-side cooling method, influence the performance of thermoelectric systems. This study aimed to investigate the effects of different hot-side cooling methods on the thermoelectric performance and thermal behavior of thermoelectric cooling systems. The testing methods involved the combination of the thermoelectric module with five hot-side heat exchangers, including a square heatsink, a round heatsink, a two-pipe heat pipe, four-pipe heat pipe, and a liquid cooler, with variations in the operating voltage. The experimental results reveal that the different heat exchangers considerably affected the system performance. The liquid cooler consistently achieved the lowest hot- and cold-side temperatures among all heat exchangers. In the case of the ratio of the cooling capacity and temperature difference across the module, the liquid cooler attained the highest values at 12 and 9 V. In addition, the square heatsink exhibited the highest ratio at 6 V. Meanwhile, the coefficient of performance (COP) values were relatively similar in the various heat exchangers, with the liquid cooler generally showing higher COP values.